Comparative Analysis of Report Presentation Finance Between Islamic Banking and Conventional Banking (Case Study at PT. Bank Syariah Mandiri and PT. Bank Mandiri) - Ardi Wirapratana; Nur Hamidah; Dwi Anto; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2023)
This research aims to determine the comparison of the presentation of financial reports between Sharia banking and conventional banking. From a conceptual perspective, these two types of banking have significant differences. Sharia banking adheres to the concept of profit sharing, while the concept of conventional banking is interest. Starting from this different concept, Sharia and Conventional banking also have different standards for presenting financial reports. The standard for presenting financial reports in Conventional banking is PSAK No. 31, while in Sharia banking it is PSAK No. 59. These different standards result in differences in the presentation of financial reports in the two types of banking. The data analysis techniques used in this research are descriptive and comparative analysis techniques. Descriptive is used to present theoretical concepts and descriptions of research objects as well as presenting data from research results. Comparative techniques are carried out by comparing financial report presentation standards between Sharia banking and conventional banking, as well as comparing each standard with practice in the field. The results of this research show that very significant differences can be seen in the Balance Sheet and Profit and Loss Reports. In Sharia banking, the liability side of the balance sheet contains items other than liabilities and equity, namely non-restricted investments. On the asset side there are musyarakah financing, mudharabah financing, murabahah receivables, istishna receivables, ijarah and Qardh. This financing and receivables occur because Sharia banking serves transactions that are not carried out by conventional banking, namely buying and selling with/without orders, renting and pawning. The most important differentiator is that the Profit and Loss Statement in Sharia banking does not present interest income and interest expenses as presented in conventional banking